Perubahan Tutupan Vegetasi Menggunakan Citra Satelit Landsat 8 dengan Metode NDVI di Kapanewon Cangkringan - Natanael Christian Hutagalung; Sugeng Wahyudiono; Yuslinawari (Jurnal Wana Tropika, 2026)
Cangkringan Subdistrict is an area in Sleman Regency located on the southern slopes of Mount Merapi. This region experiences significant land use dynamics due to volcanic activity, residential development, and community agricultural activities. These conditions can lead to changes in vegetation cover over time. Changes in vegetation cover require attention because they are related to ecosystem balance, environmental conditions, and regional spatial planning. Accurate information on vegetation conditions is essential for understanding environmental developments in a region. Therefore, remote sensing technology utilizing satellite imagery can be used as a means to effectively and periodically monitor vegetation conditions and changes. This study aims to determine the condition of vegetation cover and changes in vegetation density levels in Kapanewon Cangkringan between 2014 and 2024. The analysis was conducted using the Normalized Difference Vegetation Index (NDVI) method obtained from processing Landsat satellite imagery. The analysis process was carried out with the help of a Geographic Information System through the stages of calculating NDVI values, classifying vegetation density, and overlay analysis to see changes in vegetation cover between observation periods. The results of the study indicate that there was a change in vegetation cover during the 2014–2024 period. The area of ​​“non-vegetated land” decreased from 280.44 ha to 117.99 ha. “Low vegetation” also decreased from 3,291.48 ha to 2,837.25 ha, while “medium vegetation” increased from 903.60 ha to 1,500.30 ha. “Very low vegetation” increased from 384.93 ha to 404.91 ha.Over a period of 10 years in Kapanewon Cangkringan, there has been a decrease in "non-vegetated land" covering an area of ​​280.44 ha - 117.99 ha = 162.45 ha and "low vegetation" covering an area of ​​3,291.48 ha - 2,837.25 ha = 454.23 ha, which has increased is "medium vegetation" covering an area of ​​1,500.3 ha - 903.6 ha = 596.7 ha, and "very low vegetation" increased by an area of ​​404.91 ha - 384.93 ha = 19.96 ha. There is a dynamic change in land cover, both a decrease and an increase of 616.68 ha. If the area of ​​Kapanewon Cangkringan is 4,860.45 ha, then over 10 years there has been a dynamic change of 616.68 ha or 12.68%.